Multilingual Songbooks in Slovakia in the 19th Century - Urbancová, Hana (Traditiones, 2023)
Manuscript songbooks with a multilingual repertoire are a little-researched component of song culture from the territory of Slovakia in the 19th century. They document a tradition of multilingual singing, which survived during this period and which existed alongside singing in the Slovak language and the concept of the Slovak national song. Over the 19th century, the coexistence of several languages and the repertoire structure of these songbooks changed as the functions of singing did in contemporary society, in the given social milieu, and in a person’s life.